Grammarly and Web-based Language Learning (WBLL) in Teaching Basic Grammar - Fajriati, Retno Dwi; Rukmini, Dwi; Mujiyanto, Januarius (Universitas Negeri Semarang, 2021)
The monotonous teaching techniques lead to boredom and lack of results in teaching basic grammar. Meanwhile, technology has rapidly developed. Furthermore, different personalities, extrovert and introvert, might affect the specific result in learning a language. Therefore, this study aimed to report the effectiveness of Grammarly and Web-based language learning (WBLL) techniques in teaching basic grammar to extrovert and introvert students. It employed quantitative research with a factorial design study. The object was the first grade of Nursing and Midwifery students of Ministry of Health Polytechnic Semarang in the Academic Year of 2020/2021. It involved two experimental groups. The students in Class A were treated using Grammarly technique, and students in Class B were treated using WBLL technique. The data collection used an EPI questionnaire and pre-test and post-test. At the same time, the data analysis employed ANOVA. The result showed that Grammarly technique was more effective in teaching basic grammar to extrovert students, and WBLL technique more effective in teaching basic grammar to introvert students. The result also showed a significant value of 0.804 > 0.05. It proved that there was no significant interaction of Grammarly, Web-based language learning, and the students’ personalities in teaching basic grammar.